2015
DOI: 10.2967/jnumed.115.164442
|View full text |Cite
|
Sign up to set email alerts
|

68Ga-PSMA-HBED-CC PET for Differential Diagnosis of Suggestive Lung Lesions in Patients with Prostate Cancer

Abstract: In prostate cancer (PC) patients, the differentiation between lung metastases and lesions of different origin, for example, primary lung cancer, is a common clinical question. Herein, we investigated the use of Glu-NH-CO-NH-Lys(Ahx)-HBED-CC ( 68 Ga-PSMA-HBED-CC) for this purpose. Methods: PC patients (n 5 1,889) undergoing 68 Ga-PSMA PET/CT or PET/MR scans were evaluated retrospectively for suggestive lung lesions. For up to 5 lesions per patient, location, CT diameter, CT morphology, and SUV max were determin… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
82
0
3

Year Published

2016
2016
2021
2021

Publication Types

Select...
7
3

Relationship

2
8

Authors

Journals

citations
Cited by 114 publications
(87 citation statements)
references
References 21 publications
2
82
0
3
Order By: Relevance
“…Immunohistochemical studies reported PSMA expression in non-neoplastic regenerative tissue, ganglionic cells, and microvessels of tuberculosis lesions 3436 . Here, we describe for the first time frequent PSMA expression in dendritic cells of lymphoid follicles in Hashimoto’s thyroiditis and cervical lymph nodes.…”
Section: Discussionmentioning
confidence: 99%
“…Immunohistochemical studies reported PSMA expression in non-neoplastic regenerative tissue, ganglionic cells, and microvessels of tuberculosis lesions 3436 . Here, we describe for the first time frequent PSMA expression in dendritic cells of lymphoid follicles in Hashimoto’s thyroiditis and cervical lymph nodes.…”
Section: Discussionmentioning
confidence: 99%
“…Accordingly, there is increasing evidence that PSMA ligand uptake is not exclusively specific for PC. A large number of case series and reports describe increased PET signal in benign lesions (e.g., neurogenic tissue, Paget disease, thyroid adenoma, granulomatous disease, and adrenal adenoma) as well as in malignant diseases (e.g., renal cell carcinoma, lung cancer, glioblastoma, hepatocellular carcinoma, and thyroid cancer) (87)(88)(89)(90)(91)(92)(93)(94)(95). Supplemental Table 1 (supplemental materials are available at http://jnm.snmjournals.org) summarizes the current evidence in the literature.…”
Section: Limitations and Pitfalls In Clinical Interpretationmentioning
confidence: 99%
“…It has to be noted, however, that several reports have also described PSMA-avid lesions not related to PCa, and these differential diagnoses have to be considered when evaluating PSMA-based examinations. [12][13][14][15][16][17][18][19][20][21][22][23] However, current available clinical and preclinical studies show high image contrast and specificity, exemplarily demonstrated by this case, explaining the current fast distribution of PSMA-PET for the evaluation of PCa.…”
Section: Clinical Practice Pointsmentioning
confidence: 89%